Effects of COVID-19 and number of debtors on consumer loans in Peru - Holgado Dorado, Kilder (2022)
Objective: To evaluate whether the beginning of the COVID-19 pandemic and the variation in the number of debtors, affected the amount of current loans and the past-due portfolio of consumer loans. Method: The research was descriptive and explanatory. The analysis was documentary and statistical. To find the effect of the independent variables on the dependent variables, the ordinary least squares model was used, where the COVID-19 period took the value of 1 and 0 was considered in any other case; in addition, the evaluated period was from September 2018 to September 2021. Results: The start of the COVID-19 pandemic caused a decrease in current loans and an increase in the past-due portfolio. Conclusions: The rescheduling of loans in the current portfolio, due to the start of the COVID-19 pandemic, prevented an increase in bank provisions; however, the impact of the rescheduling in each bank was different, increasing the overdue portfolio.